PENGEMBANGAN LIFE SKILLS BAGI MAHASISWA PENDIDIKAN AGAMA ISLAM ( PAI ) - Muhammad Zakki Aghnia; Muhammad Maulana Ishak; Wafiq Dwi Maulidina; Lili Hasanah; Munasir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are crucial for students in the 21st century. Identifying problems, selecting and evaluating them, organizing them, and finding logical solutions are all examples of critical thinking skills. This quantitative descriptive study focused on the Islamic Religious Education Department of the Faculty of Tarbiyah at the Miftahul Huda Institute in Subang. The researchers found that students who took Islamic Religious Education classes had better critical thinking skills. Data were collected using a questionnaire. Problem-based and project-based learning models are two models that can be used to improve students' critical thinking skills. Four indicators of excellent critical thinking were studied, including students' ability to identify and analyze problems, their ability to behave and think critically, and their ability to find creative and logical solutions to real-life problems. Cognitive skills such as critical, creative, and solution-oriented thinking; social skills such as communication, collaboration, and empathy; emotional skills such as self-control, adaptability, and mental resilience; and practical skills such as time management, digital literacy, and entrepreneurship. This curriculum is designed to focus on student performance and incorporate unique courses for each course, as well as life skills. Active learning can be seen in case discussions, projects, and problem-solving. Coaching, mentoring, and collaboration enhance student organization and the campus environment. PAI graduates who develop life skills aligned with Islamic values ​​such as mas'uliyah (responsibility), amar ma'ruf nahi munkar (commanding good and forbidding evil), and istikamah (steadfastness) will be individuals who possess not only academic and spiritual abilities but also flexibility, contribution, and the ability to address contemporary issues.